Time Course and Magnitude of Movement-Related Gating of Tactile Detection in Humans. II. Effects of Stimulus Intensity - Williams, Stephan R; Chapman, C. Elaine (Journal of neurophysiology, 2000)
1 Centre de Recherche en Sciences Neurologiques,   2 Département de Physiologie, and   3 École de Réadaptation, Faculté de Médecine, Université de Montréal, Montreal, Quebec H3C 3J7, Canada Williams, Stephan R. and C. Elaine Chapman. Time Course and Magnitude of Movement-Related Gating of Tactile Detection in Humans. II. Effects of Stimulus Intensity. J. Neurophysiol. 84: 863-875, 2000. This study examined the effect of systematically varying stimulus intensity on the time course and magnitude of movement-related gating of tactile detection and scaling in 17 human subjects trained to perform a rapid abduction of the right index finger (D2) in response to a visual cue. Electrical stimulation was delivered to D2 at five different intensities. At the lowest intensity, approximately 90% of stimuli were detected at rest (1 × P 90 ); four multiples of this intensity were also tested (1.25, 1.5,   1.75, and 2.0 × P 90 ). At all intensities of stimulation, detection of stimuli applied to the moving digit was diminished significantly and in a time-dependent manner, with peak decreases occurring within ±12 ms of the onset of electromyographic activity in the first dorsal interosseous (25-45 ms before movement onset). Reductions in the proportion of stimuli detected were greatest at the lowest stimulus intensity and progressively smaller at higher intensities. No shift in the timing of the decreases in performance was seen with increasing intensity. Once the weakest intensity at which most stimuli were perceived during movement had been established (2 × P 90 ), magnitude estimation experiments were performed using two stimulus intensities, 2 × P 90 (5 subjects) and 3 × P 90 (3   subjects). Significant movement-related decreases in estimated stimulus magnitude were observed at both intensities, the time course of which was similar to the time course of reductions in detection performance. As stimulus intensity increased, the magnitude of the movement-related decrease in scaling diminished. A model of detection performance that accurately described the effect of stimulus intensity and timing on movement-related reductions in detection was created. This model was then combined with a previous model that described the effects of stimulus localization and timing to predict detection performance at a given stimulation site, intensity, and time during movement. Movement-related gating of tactile perception represents the end result of movement-related effects on the transmission and subsequent processing of the stimulus. The combined model clearly defines many of the requirements that proposed physiological mechanisms of movement-related gating will have to fulfill.